Analisis Bibliometrik Tren Penggunaan Lahan di Daerah Aliran Sungai Berbasis Penginderaan Jauh: Perspektif Global 2020–2024 - Tahir, Tahir; Yusuf, Daud; Akbar, La Ode Juni (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Land use in Watersheds (DAS) is a crucial aspect of environmental research due to its impact on water quality, ecosystem sustainability, and food security. In recent years, remote sensing technology has advanced significantly, offering efficient spatial analysis capabilities to monitor land use changes in watersheds. However, despite the numerous studies conducted, knowledge gaps remain, particularly in understanding thematic trends and global collaboration networks during the 2020–2024 period. This study presents a bibliometric analysis of articles indexed in Scopus to identify key themes, temporal trends, dominant authors, citation counts, and inter-country collaborations in this field. Data were analyzed using the Vosviewer software to visualize the distribution of themes such as remote sensing, GIS, and land cover, as well as focus areas like the Yellow River Basin and the United States. The findings reveal that remote sensing emerges as a central theme, with modern technologies such as Landsat and Google Earth Engine playing a critical role in environmental monitoring. Intense international collaboration is observed among developed countries such as China and the United States, while developing countries like Indonesia contribute to local contexts. This study provides in-depth insights into the trends of land use research in watersheds, supports data-driven decision-making, and promotes environmental sustainability through more adaptive watershed management